SOCIO-PSYCHOLOGICAL MECHANISMS OF MOBILE PHONE ADDICTION AMONG UNIVERSITY STUDENTS (European Journal of Interdisciplinary Research and Development, 2026)
This article analyzes the socio-psychological mechanisms influencing the formation of mobile phone addiction among university students. The study highlights the impact of excessive use of mobile devices on personal development, social relationships, emotional states, and self-regulation processes. In addition, the motivational factors of mobile phone addiction, individuals’ psychological needs, social environment, peer influence, and the effects of virtual communication on real-life relationships are theoretically examined. The article also presents conclusions on psychological prevention and correction strategies aimed at fostering conscious and moderate use of mobile technologie